Synthesis, crystal structure, HF and DFT calculations of 1-(2-chlorobenzyl)-N-(1-(2-chlorobenzyl)-4,5-dihydro-1H-imidazol-2-yl)-1H-benzimidazol-2-amine - Yuksektepe, Cigdem; Caliskan, Nezihe; Genc, Murat; Servi, Suleyman (Pleiades Publishing Inc, 2010)
The titled compound (1), has been synthesized and characterized by IR and H-1-NMR spectroscopy, and single crystal X-ray diffraction. The compound crystallizes in the triclinic space group P-1. The crystal structure is stabilized by C-HaEuro broken vertical bar pi and aromatic pi-pi interactions. There are also intramolecular N-HaEuro broken vertical bar N and C-HaEuro broken vertical bar N hydrogen bonds in the molecule. The use of quantum chemical calculations to characterise and optimise the choice of material is illustrated by ab initio treatments. Vibrational frequencies and LUMO-HOMO energy difference of 1 have also been investigated by Density functional theory (DFT) and Hartree-Fock (HF) calculations. Calculated frequencies are in good agreement with the corresponding experimental data.
Keywords: Benzimidazole; IR spectra; crystal structure; HOMO and LUMO energy; DFT and HF calculations